PENGEMBANGAN MODEL PEMBELAJARAN VIRTUAL (MPV) BERBASIS VIDEO E-LEARNING MOODLE - Hade Afriansyah (Universitas Negeri Padang, 2019)
This study aims to develop a learning model by using web-based moodle e-learning videos to support student learning outcomes in Computer subject. This research is motivated by the development of technology increasing rapidly, the demand for efficiency is increasing. Video e-learning media is a very good breakthrough, and demands for modernization in the world of education. The research method in this study was conducted using the R and D method. The study began with preparing teaching materials that were previously used, preparing teaching materials from the latest sources, collaborating old teaching materials with new teaching materials, reviewing instructional materials that have been compiled, refining materials teach according to directions, make video tutorials based on teaching materials, tutorial videos that have been uploaded to youtube, video links that have been uploaded on youtube are combined with e learning, the final step is done by perfecting the web-based e learning video teaching material by doing several test times , evaluating, and correcting as needed. Keywords: learning models, video learning, moodle e-learning